1990
DOI: 10.1039/ja9900500705
|View full text |Cite
|
Sign up to set email alerts
|

Determination of selenium in human serum using a direct hollow-cathode discharge atomic emission spectrographic technique

Abstract: Samples of serum and a series of aqueous standards of SeOp were dried on to the wall of an aluminium cathode cup at a temperature of 293 K, thus ensuring a sample preparation procedure without loss of analyte. Using the Se II 444.62-nm and Se II 444.95-nm spectral lines, the detection limit for the proposed method was established as being 1 ng ml-l. The selenium content of the samples varied between 80 and 120 ng ml-1, which is two orders of magnitude higher than the detection limit of the proposed method. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1993
1993
2001
2001

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…148,211 To avoid possible losses of Se from hot HC1 solutions, the hydroxylammonium chloride method has been used, which also reduces Fe(III) into Fe(II), so eliminating interference by the former and preventing hightemperature oxidization of DAN. 136 Many authors104,140,150,212 have indicated that the pH optimum in the formation of piazselenole is between 1-2 or certain values between 1 and 2_134, 136,148,169,170,174,179,189,190,204,205,213 Bayfield et al 197 have studied the pH control with diverse indicators in the reaction mixture following acid digestion of samples and preceding formation of the piazselenole complex. Maximal fluorescence response is achieved by using methyl orange as an internal indicator to establish an initial pH of 3 and, after addition of the DAN reagent in 0.1 N HC1, a final pH of 1.8.…”
Section: Determination Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…148,211 To avoid possible losses of Se from hot HC1 solutions, the hydroxylammonium chloride method has been used, which also reduces Fe(III) into Fe(II), so eliminating interference by the former and preventing hightemperature oxidization of DAN. 136 Many authors104,140,150,212 have indicated that the pH optimum in the formation of piazselenole is between 1-2 or certain values between 1 and 2_134, 136,148,169,170,174,179,189,190,204,205,213 Bayfield et al 197 have studied the pH control with diverse indicators in the reaction mixture following acid digestion of samples and preceding formation of the piazselenole complex. Maximal fluorescence response is achieved by using methyl orange as an internal indicator to establish an initial pH of 3 and, after addition of the DAN reagent in 0.1 N HC1, a final pH of 1.8.…”
Section: Determination Proceduresmentioning
confidence: 99%
“…The Na content of the serum was lower than the concentration which can cause a decrease in the spectral line intensity. 213 A most promising analytical technique in recent years has been the development of the plasma source for emission spectrometry. In ICP technique, no physical interferences were found,339 but the Se 196.026 nm lines have a significant baseline structure in an aqueous matrix, which is greatly reduced when the optical path is purged with N2.…”
Section: Hg-aasmentioning
confidence: 99%
“…Volumes of the liquid samples were introduced by a micropipette into the cathode cavity and dried under an infrared lamp, under continuous rotation in order to deposit solution residues uniformly, and then ignited in a muffle furnace. Se in human serum 5 has also been determined by dc-GD-OES, while elemental analyses of urine samples 6 has also been reported by GD-mass spectrometry (MS) after adequate drying of such liquid samples.…”
Section: Introductionmentioning
confidence: 99%